(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Natalya B. Boeva-Omelechko (Southern Federal University, Rostovon-Don, Russian Federation) The article focuses on the phenomenon of political modalization as an immanent feature of socio-political media discourse. Political modalization is not restricted to modality in the narrow, traditional sense and presupposes ideological interpretation of facts and events described in texts of the discourse in question. This interpretation can be directly contrary in oppositional discourses. Due to it contrast pictures of the world are created in the minds of recipients. Especially it concerns such modal objects as states. The article reveals linguistic means used for creating two images of America which stand in opposition to each other in American and Russian socio-political media discourses. These means include utterances with explicit evaluations (axiological means of modalization), microcontexts where the name of America is regularly used with names of negatively or positively evaluated phenomena (syntagmatic associative means of modalization) and conceptual metaphors with negative or positive connotations (metaphoric means of modalization). In American socio-political discourse these means help to represent the USA as an exceptional superpower playing the vital role in the struggle for freedom, justice and peace. In contrast to it Russian sociopolitical discourse represents America as an aggressive country which seeks to dominate the world through wars, threats, pressure on other countries. In this discourse America is associated with chaos, the unpredictability, avantyurizm, political deafness. It is concluded that political modalization is a powerful means of influence and effective means of its realization are worth studying. Key words: socio-political media discourse, political modalization, contrast, America, axiological, syntagmatic associative, metaphoric means of modalization, conceptual metaphor. DOI 10.23683/1995-0640-2017-2-178-186